Dietary Factors and Neurodegenerative Disorders: An Umbrella Review of Meta-Analyses of Prospective Studies. Issue 5 (19th May 2020) - Barbaresko, Janett; Lellmann, Arno Werner; Schmidt, Annemarie; Lehmann, Andreas; Amini, Anna Maria; Egert, Sarah; Schlesinger, Sabrina; Nöthlings, Ute
ABSTRACT: Diet has been hypothesized to be associated with neurodegenerative disorders. The aim was to conduct an umbrella review to summarize and evaluate the current evidence of prospective associations between any dietary factors and the incidence of neurodegenerative disorders. We conducted a systematic search in PubMed, Embase, and the Cochrane library up to November 2019 to identify systematic reviews with meta-analyses of prospective studies investigating the association between dietary factors (dietary patterns, foods and beverages, nutrients, and phytochemicals) and neurodegenerative disorders (cognitive decline, cognitive impairment, Alzheimer disease, all-cause dementia, and Parkinson disease). Summary risk ratios (SRRs) and 95% CIs were recalculated using a random effects model. We evaluated the risk of bias of identified meta-analyses and the quality of evidence for all associations. In total, 20 meta-analyses including 98 SRRs were identified. All original meta-analyses were rated as being at high risk of bias. Methodological concerns related mainly to the inappropriate synthesis, assessment, and discussion of the risk of bias of primary studies. For the recalculated meta-analyses, quality of evidence was moderate for inverse associations between higher adherence to the Mediterranean diet (SRR: 0.63; 95% CI: 0.48, 0.82; n = 4 primary studies) and higher fish intake (SRR: 0.72; 95% CI: 0.59, 0.89; n = 6) and Alzheimer disease, as well as for tea consumption and all-cause dementia (SRR: 0.74; 95% CI: 0.63, 0.88; n = 2) and Parkinson disease (SRR per 2 cups/d: 0.69; 95% CI: 0.54, 0.87; n = 5). This umbrella review provides a comprehensive overview of the available evidence on dietary factors and neurodegenerative disorders. The results indicate that the Mediterranean diet, fish, and tea could be inversely associated with neurodegenerative disorders. However, the quality of evidence was generally low, suggesting that further studies are likely to change the overall estimates. Thus, more well-conducted research, also investigating other dietary factors in association with neurodegenerative disorders, is warranted. Abstract : This umbrella review provides an overview of the currently available evidence on dietary factors and neurodegenerative disorders derived from meta-analyses of prospective studies.